Aktivitas fisik dan psikologis pada pasien chronic kidney disease yang menjalani hemodialisis: A literature review - Pangaribuan, Resmi; Tarigan, Almina Rospitaria; Anggeria, Elis; Girsang, Ermi; Gea, Saharman (Holistik Jurnal Kesehatan, 2025)
Background: Chronic kidney disease (CKD) is a condition in which kidney function gradually declines or is even lost completely. This decline in kidney function can lead to fluid and metabolic waste accumulation in the body, which, if not properly managed, can progress to end-stage kidney failure, requiring renal replacement therapy in the form of dialysis or a kidney transplant. For patients with chronic kidney disease (CKD), the presence of caregivers and family members is the most important source of support. Purpose: To determine the physical and psychological impact of CKD on patients undergoing hemodialysis. Method: This literature review utilized databases such as PubMed, Google Scholar, and Science Direct and included articles published between 2020 and 2024. Inclusion criteria included studies discussing physical activity, quality of life, and psychological aspects in CKD patients undergoing hemodialysis. Studies not available in English or Indonesian, as well as studies not relevant to the topic, were assessed in this review. The search yielded 14 articles, which were selected through keyword selection. Results: Physical activity is an important treatment and prevention measure for chronic kidney disease. The concept of "exercise as medicine" emphasizes that exercise not only helps improve physical function and muscle strength but also provides positive benefits in slowing the progression of chronic diseases. Conclusion: Physical activity such as aerobic exercise, resistance training, and other light exercise can reduce levels of depression and anxiety, improve sleep quality, and enhance perceived quality of life. Suggestion: More longitudinal studies and randomized controlled trials (RCTs) are needed in Indonesia or other developing countries to assess the effectiveness of physical activity-based programs on the psychological aspects of CKD patients.   Keywords: Chronic Kidney Disease; Hemodialysis; Psychological; Physical Activity.   Pendahuluan: Gagal ginjal kronis adalah suatu kondisi ketika fungsi ginjal secara bertahap menurun atau bahkan hilang sepenuhnya. Turunnya fungsi ginjal dapat menyebabkan penumpukan cairan dan sisa metabolisme dalam tubuh yang apabila tidak ditangani dengan baik akan berkembang menjadi gagal ginjal stadium akhir, membutuhkan terapi pengganti ginjal berupa dialisis atau transplantasi ginjal. Bagi pasien gagal ginjal kronis, kehadiran perawat dan keluarga merupakan sumber dukungan yang paling utama. Tujuan: Untuk mengetahui aktivitas fisik  dan psikologis pada pasien chronic kidney disease yang menjalani hemodialisis. Metode: Penelitian literature review menggunakan database dari pubmed, google scholar dan science direct, artikel diterbitkan antara 2020-2024. Kriteria inklusi yang digunakan mencakup studi yang membahas aktivitas fisik, kualitas hidup, dan aspek psikologis pada pasien PGK yang menjalani hemodialisis. Studi yang tidak tersedia dalam bahasa Inggris atau Indonesia, serta yang tidak relevan dengan topik, dikecualikan dari review ini. Pencarian yang diperoleh dari seleksi penilaian dan kata kunci sebanyak 14 artikel. Hasil: Aktivitas fisik merupakan pengobatan dan tindakan pencegahan yang penting untuk penyakit. Konsep “olahraga sebagai obat” menekankan bahwa olahraga tidak hanya membantu meningkatkan fungsi fisik dan kekuatan otot, tetapi juga memberikan manfaat positif untuk memperlambat perkembangan penyakit kronis. Simpulan: Aktivitas fisik seperti latihan aerobik, resistensi, dan latihan ringan lainnya mampu menurunkan tingkat depresi dan kecemasan, meningkatkan kualitas tidur serta persepsi kualitas hidup. Saran: Diperlukan lebih banyak studi longitudinal dan uji coba terkontrol secara acak (RCT) di Indonesia atau negara berkembang lainnya untuk menilai efektivitas program berbasis aktivitas fisik pada aspek psikologis pasien CKD.   Kata Kunci: Aktivitas Fisik; Chronic Kidney Disease; Hemodialisis; Psikologis.